Taxonomic update of Magnolia subsect. Talauma (Magnoliaceae) from Cuba - Testé, Ernesto; García-Beltrán, José Angel; Palmarola, Alejandro; Robert, Thierry; Bécquer, Eldis R. (Phytotaxa, 2023)
The taxonomy of Magnolia subsect. Talauma in Cuba has long been debated with many changes in the last few years. New evidence based on ecological, morphological and genetic data has indicated the occurrence of three taxa, with changes in the limits from the latest taxonomic treatment. In this sense, the taxonomy and nomenclature of Magnolia subsect. Talauma in Cuba is reviewed. Diagnoses of all taxa are presented with an identification key, nomenclatural information and distribution. Magnolia subsect. Talauma in Cuba comprises three endemic species: Magnolia orbiculata, M. minor and M. oblongifolia. Magnolia orbiculata is the only species that keeps the same limits as in the previous taxonomic treatments of the group, whereas it is not the same for the northeastern Cuban species.